2019
DOI: 10.1002/osi2.1014
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment, particle radiotherapy, and boron neutron capture therapy for advanced oral cancer in patients

Abstract: Malignant tumors such as squamous cell carcinoma (SCC), malignant salivary gland tumor, mucosal melanoma, sarcoma, and lymphoma occur in the oral cavity. Among them, oral SCC accounts for 90%. The frequency of lymph node metastasis of oral SCC varies depending on the site of occurrence, which affects the prognosis. Surgery is the primary treatment for oral cancer, but when the tumor extends, postoperative radiation with or without chemotherapy is required. Photons including X-rays and γ-rays are the most widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 232 publications
0
2
0
Order By: Relevance
“…A characteristic of treatment for HNSCC is the application of photon radiotherapy with gamma rays and X-rays. Although it is possible to irradiate a high dose of 6-13 Gy equivalent in particle radiotherapy using proton or carbon beams [204,205], each irradiation dose in fractionated X-ray radiotherapy for head and neck cancer is usually 2 Gy [206]. Previous studies reported that ceramide production in tumors and tumor vessels was low at an irradiation dose of 2 Gy [99,207].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A characteristic of treatment for HNSCC is the application of photon radiotherapy with gamma rays and X-rays. Although it is possible to irradiate a high dose of 6-13 Gy equivalent in particle radiotherapy using proton or carbon beams [204,205], each irradiation dose in fractionated X-ray radiotherapy for head and neck cancer is usually 2 Gy [206]. Previous studies reported that ceramide production in tumors and tumor vessels was low at an irradiation dose of 2 Gy [99,207].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Nivolumab and pembrolizumab are FDA-approved anti-PD-1 antibodies against HNSCC [1]. In resectable oral squamous cell carcinoma in HNSCC, radical resection and reconstructive surgery are usually performed, although radical cure by heavy ion radiotherapy has been Cancers 2022, 14, 792 2 of 25 also attempted [2][3][4][5]. If risk factors for recurrence are confirmed after surgery, additional chemoradiotherapy is given [6].…”
Section: Introductionmentioning
confidence: 99%